Application of Meat Post-Harvest Technology By The Housewife Group In Kendari City - patriani, peni patriani (Journal of Saintech Transfer, 2023)
Community service aims to provide a comprehensive understanding for the housewife group in Gunungjati Sub-District around Kendari City Market regarding the management of healthy food and livestock products. This activity is expected to provide knowledge and skills related to fresh meat and its processing to obtain food diversification, increase nutritional value, longer shelf life, and added economic value. The method used was training and direct demonstration related to fresh, preserved, and rotten meat as well as the processing of nuggets and sausage. Various meats can be used to make nuggets and sausages such as chicken, beef and buffalo meat. Training materials were related to the importance of consuming fresh meat, the importance of choosing uncontaminated meat with preservatives, and processed livestock products in the form of nuggets and sausages with benefits for human health and can be a source of family income. This activity has a positive impact to make people creative with meat-based ingredients and motivates them to create a business field. The types of meat that have been used for the development of sausage and nugget products are beef, rejected chicken meat and broiler chicken meat